2006
DOI: 10.1080/17482620600601187
|View full text |Cite
|
Sign up to set email alerts
|

Swedish assistant nurses’ experiences of job satisfaction when caring for persons suffering from dementia and behavioural disturbances. An interview study

Abstract: Job satisfaction is complex and is an important component in facilitating high quality nursing care. Behavioural and psychological symptoms of dementia (BPSD) can be clustered into one of five syndromes: psychosis, aggression, psychomotor agitation, depression and apathy, and comprise signs and symptoms of disturbed perception, thought content, mood or behaviour that frequently occur in patients with dementia. BPSD can cause tremendous distress both for the patients and for their caregivers and they have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…(33) A group of nurse assistants reported that the administration in their facility made them feel like an extra cost, in contrast with their co-workers by whom they felt valued. (49) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(33) A group of nurse assistants reported that the administration in their facility made them feel like an extra cost, in contrast with their co-workers by whom they felt valued. (49) …”
Section: Resultsmentioning
confidence: 99%
“…(34,49) A lack of education and training impacted nurses and nurse trainees whose reactions to symptoms or behaviours might range from sadness to fear of the patients. (35,40) …”
Section: Resultsmentioning
confidence: 99%
“…Kristiansen et al [4] consider that one possible way to reduce the prevalence of BPSD-related violence is to develop education, leadership, supervision and reflection. This could also be a way to increase the well-being of the nurses and increase their job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…BPSD includes many different symptoms such as screaming, restlessness, wandering, anxiety, apathy, depression, hallucinations, sleep disturbance and agitation [2] [3]. The frequency and severity of the BPSD symptoms are highly associated with caregiver burden and reducing quality of life for both the person with dementia and their caregivers [2] [4].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding workers' experiences can help to identify appropriate support, which in turn can positively influence their satisfaction and wellbeing (e.g. Kristiansen, Hellzén, & Asplund, 2006;Stockwell-Smith, Jones, & Moyle, 2011). 7 Existing research with dementia volunteers has identified issues relating to a) volunteers' role, particularly regarding the need for role clarity, b) emotional experiences, including emotional reward, acceptance of their own experiences, fear of rejection and difficulties ending the relationship, c) personal development, such as increased empathy and appreciation of clients, and d) professional support in terms of the need for specific training (Chung, 2008;Greenwood et al, 2013;Guerra, Demain, Figueiredo & De Sousa, 2012;Pillemer, Landreneau, & Suitor, 1996;Tanner & Brett, 2014).…”
Section: Research With Volunteersmentioning
confidence: 99%